Helminth Fauna of Roe Deer (Capreolus capreolus) in Ukraine: Biodiversity and Parasite Community - Kuzmina, T.A.; Kharchenko, V.A.; Malega, A.M. (Вестник зоологии, 2010)
The results of survey of helminth species diversity of roe deer (Capreolus capreolus Linnaeus, 1758) from nine regions of Ukraine are presented. Ninetytwo roe deer from Chernigivska, Zhytomyrska, Kyivska, Vinnytska, Rivnenska, Ternopilska, Khmelnitska, Sumska and Cherkasska regions were examined by the partial helminthological dissection. Totally 30,753 helminth specimens were collected and identified by morphological criteria. Prevalence of roe deer infection with helminths was 92.4%. Sixteen helminth species (1 of the Class Trematoda, 2 — of Cestoda and 13 — of Nematoda) were found. Setaria cervi (prevalence — 10.9%) was found in visceral cavity. Dictyocaulus eckerti (6.9%) and D. capreolus (2.3%) was found in lungs. Taenia hydatigena larvae (2.3%) were found in mesentery. Paramfistomum cervi (10.9%), Haemonchus contortus (57.6%), Ashworthius sidemi (40.2%), Marshallagia marshalli (15.2%), Nematodirus oiratinus (1.1%), Trichostrongylus axei (3.3%) were found in stomach. Moniesia expansa (1.1%), Bunostomum phlebotomum (10.9%) were found in small intestine. Trichocephalus ovis (18.5%), Oesophagostomum venulosum (7.6%) and O. dentatum (1.1%) were found in caecum. Chabertia ovina (28.3%) was found in large intestine. Forty-four helminth associations were separated in the roe deer examined.